INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SISWA KELAS VII DI SEKOLAH MENENGAH PERTAMA ISLAM AL AKBAR SINGOSARI - Annisa 'Uliya Rahmah (VICRATINA, 2022)
This research is due by the motivation of innovations made by Islamic Religious Education teachers in learning process at Al Akbar Islamic Junior High School Singosari. This study aims to describe the design of Islamic religious education learning in seventh grade students at Al Akbar Singosari Islamic Middle School, to describe the implementation of Islamic religious education learning to VII grade students at Al Akbar Singosari Islamic Junior High School and also to describe the evaluation of Islamic religious education learning in grade students. VII at Al Akbar Singosari Islamic Junior High School. This research use a qualitative approach. And in collecting data, researchers use the observation, interviews, and documentation method. For the analysis technic, the author uses a qualitative descriptive analysis technique in the form of written or oral data. Based on the results of the research, it is known that the learning design carried out by Islamic Religious Education teachers at Al Akbar Singosari Islamic Junior High School is in accordance with how to prepare a good lesson plan (RPP) and is also in accordance with the applicable curriculum. The implementation of learning in Islamic Religious Education learning at Al Akbar Singosari Islamic Junior High School, the teacher use a lot of variety learning methods. In addition, the teacher also does the habituation of religious character values.